Pelatihan Politik Hukum Perlindungan Lahan Pertanian dan Hak Asasi Petani dalam Konsep Urban Farmingdi Kecamatan Medan Labuhan Kota Medan Provinsi Sumatera Utara - Sarminta; Sinabariba, Darwin; Zulkarnain, Novi Juli Rosani (SABA JAYA PUBLISHER, 2024)
Political and Legal Training for Agricultural Land Protection and Farmers' Human Rights in the Urban Farming Concept in Medan Labuhan District, Medan City, North Sumatra Province, is an effort to increase understanding and implementation of the urban farming concept. This activity is carried out by involving counseling and demonstrations, discussing legal politics that support the protection of agricultural land and farmers' human rights. Through surveys and initial interviews, it was revealed that public awareness, especially farmers, of the potential of yards for food farming is still lacking. Urban farming was identified as a solution to optimize yard land and improve farmers' welfare. The training activity succeeded in conveying insight into legal politics and received a positive response from the participants. The results of the activity showed the participants' high interest and enthusiasm in understanding urban farming techniques and concepts. This training not only provides knowledge of legal politics and agricultural land protection, but also inspires the adoption of urban farming. In conclusion, it is hoped that this training can improve local food security, farmer welfare and environmental preservation through the implementation of sustainable urban farming in cities.